Relevance of Microorganisms in Causing Rain and Snow - Kaul, Rimple; Devi, Sunita; Sharma, Megha; Chand, Subhash (Recent Patents on Biotechnology, 2025)
Various natural phenomena (such as solar fluctuations, oceanic patterns, volcanic eruptions, and tectonic movements) alongside human activities (including deforestation, CO and CO2 emissions, and desertification) contribute to ongoing climate change and subsequent global warming. However, human actions significantly exacerbate global warming, amplifying its adverse impacts worldwide. With rising temperatures, water evaporation from water bodies and soils intensifies, leading to heightened water scarcity, particularly in drought-prone regions. This scarcity compounds rainfall deficits, posing significant challenges. Precipitation, essential for the biosphere's hydrological cycle, replenishes much of the world's freshwater. It occurs when condensed water vapor in the atmosphere falls back to Earth as rain, drizzle, sleet, graupel, hail, or snow due to gravity. Literature highlights the indispensable role of microbial populations in this process, termed bio-precipitation. This phenomenon begins with microbial colonization on plant surfaces, with colonies subsequently dispersed into the atmosphere by winds, triggering ice crystal formation. Through their ice nucleating property, these microbes facilitate the growth of larger ice crystals, which eventually melt and precipitate as rain or snow. This mechanism aids in nutrient transfer from clouds to soil or vegetation. Pseudomonas syringae stands out as the most notable microorganism exhibiting this ice-nucleation property, serving as the primary source of ice nucleators driving bio-precipitation. Despite limited literature on “rain and snow-causing microorganisms,” this review comprehensively explores the conceptual background of bio-precipitation, the involved bio-processes, and the critical role of bacteria like P. syringae, offering insights into future research directions and patent innovations.
Keywords: snow-causing microorganisms